After Agonistic Liberalism: Milbank and Pabst's Relentless Pursuit of Radical Anglican Thomism. (May 2019) - Song, Robert
Milbank and Pabst's account of liberalism as rooted in ontological violence picks out the secret commonalities of left-leaning rights-based and right-leaning market-based liberalisms with considerable shrewdness, and their elaboration of associationist and civil economic alternatives contains many strikingly expansive and novel elements. However, their totalising account of liberalism prevents them from engaging the strengths of the liberal era with sufficient generosity, and so impedes their efforts to articulate a way forward that is substantially and not just chronologically post-liberal.